Eksplorasi Harga Bahan Pokok sebagai Indikator Dini Pengendalian Inflasi di Sumatera Barat - Fauzi, Kory Rahmat; Salim, Agus; Satria, Doni (Universitas Negeri Padang, 2023)
This study explores inflation’s leading indicators in West Sumatra using ten strategic commodities prices. These ten strategic commodities are rice, beef, chicken meat, chicken egg, onion, garlic, red chili, cayenne pepper, cooking oil, and sugar. This study employs the Granger Causality Test to infer the inflation’s leading indicators in West Sumatra using monthly time series data from August 2017 up to December 2021. The results show red chili and chicken meat have a positive and significant effect on inflation in West Sumatra and can be used as Leading Indicators of West Sumatra inflation. The main implication of this finding is the inflation rate would be as volatile as red chili and chicken meat prices.